Management Approach Analysis in Professional Nursing Practice Model and Nurse Work Satisfaction on Nurse Performance in Room Interpreting X Hospital - Riyan Prawira Sentana (Universitas Muhammadiyah Yogyakarta, 2017)
X Hospital Bantul is a type C hospital that has a capacity of 129 beds with a total of 173 nurses. As a health worker who provides nursing services for 24 hours, nurses contribute greatly in improving the quality of service in hospitals. The purpose of this study is to determine the effect of the chief management approach and nurses job satisfaction on the performance of the nurses in the inpatient ward of X Hospital. The population of all nurses in the inpatient ward. The sample size was 101 nurses in the inpatient ward. Data analysis using linear regression. Result of t test of management approach obtained t value equal to 5,393 (5,393> 1,984) and obtained t count value equal to 2,916 (2,916> 1,984) which mean approach of management and job satisfaction partially have significant influence to nurse performance. While F test result obtained by F value 21.135 (21,135> 3,089) with p value (0,000), which means there is a significant effect together the approach of chief management of space and job satisfaction on the performance of nurses in hospital ward PKU Muhammadiyah Bantul. The conclusion of management approach and job satisfaction has a significant effect on the performance of nurses at X Hospital.